CORRELATION AND INFLUENCE ANALYSIS BETWEEN JOB CHARACTERISTICS AND PUBLIC SERVICE MOTIVATION (Journal of Governance and Development (JGD), 2022)
Earlier studies point out that staff member performance can be affected by their motivation. Public service motivation is believed to be one of the internal motivations influencing staff member performance. This study aims to analyze the relationship and influence between job characteristics and public service motivation among civil servants in Jakarta. A mix of quantitative and qualitative approaches was used in the study as tools of analysis. The respondents were 951 civil servants coming from 3 different agencies with the highest income in Jakarta (the DKI Jakarta Provincial Government, the Directorate General of Taxes, and the Directorate General of Immigration. The result of this study shows that there are only four dimensions of job characteristics that have a significant relationship and influence on public service motivation, i.e.: 1) skill variety; 2) task significance; 3) autonomy; 4) feedback. Meanwhile, the task identity dimension showed no influence on public service motivation.